Digital Storytelling in Extracurricular Activities in Biology - Franchuk-Kryva, Liubov; Gvozdii, Svitlana (Educological discourse, 2023)
The article is devoted to topical issues of extracurricular activities using digital storytelling. The purpose of the article is to determine the feasibility of using digital storytelling in extracurricular activities in biology. Today, a modern biology teacher must provide students with the subject knowledge necessary to understand the scientific and natural picture of the world, to form a competent attitude to their health and the health of others, to behave in an environmentally responsible manner in nature and to solve life problems. At the same time, the subject of biology is diverse and dynamic, which leads to a rich curriculum and a constant increase in the amount of information to be learned and requires new approaches not only to classroom but also to extracurricular activities. The article emphasises that a successful combination of traditional teaching methods and information and communication technologies, considering their didactic advantages, can significantly enrich and diversify the content of extracurricular activities in biology. One of such ways may be the use of digital storytelling technology, which is increasingly being used by domestic teachers. The basic requirements for the preparation and planning of extracurricular activities in biology using digital storytelling are outlined. Platforms and applications that can be used as a digital storytelling tool are identified. Examples for different classes of basic school are proposed, which can serve as a basis for further development of extracurricular activities for modern biology teachers. The article presents a broad analysis of domestic and foreign researchers who note that digital storytelling as a pedagogical tool helps to expand the cognitive and communication capabilities of students, activates attention and memory, promotes individualisation of learning, cognitive independence, develops the ability to think creatively, provides friendly, collective relationships and can be used in working with students of different age groups.